Colorimetric metal-free detection of carbon monoxide: reversible CO uptake by a BNB frustrated Lewis pair - Zheng, X; Zulkifly, I; Heilmann, A; McManus, C; Aldridge, S (Wiley, 2021)
We report two BNB-type frustrated Lewis pairs which feature an acceptor-donor-acceptor functionalized cavity, and which differ in the nature of the B-bound fluoroaryl group (C6F5 vs. C6H3(CF3)2-3,5, Arf). These receptor systems are capable of capturing gaseous CO, and in the case of the -BArf2 system this can be shown to occur in reversible fashion at/above room temperature. For both systems, the binding event is accompanied by migration of one of the aryl substituents to the electrophilic carbon of the CO guest. Experiments utilizing an additional equivalent of PtBu3 allow the initially formed (non-migrated) CO adduct to be identified and trapped (via demethylation), while also establishing the reversibility of the B-to-C migration process. When partnered with the slightly less Lewis acidic -BArf2 substituent, this reversibility allows for release of the captured carbon monoxide in the temperature range 40–70 °C, and the possibility for CO sensing, making use of the associated colourless to orange/red colour change.